(untitled) (Bangladesh Journal of Medical Microbiology, 2012)
Isolation and identification of post operative hospital acquired infection was carried out from July 2008 to December 2008 in Holy Family Red Crescent Medical College Hospital (private hospital). The major pathogen of wound infection was E. coli. A total; of 120 samples were collected from the surrounding environment of post operative room like floor, bed sheets, instruments, dressing materials, catheter, nasogastric and endotracheal tube. E. coli (40%) was the predominant organism followed by S. aureus (24%). DNA fingerprinting analysis using pulsed field gel electreopheresis of XbaI restriction digested genomic DNA showed that clonal relatedness between the two clinical nd environmental isolates were 100%. DOI: http://dx.doi.org/10.3329/bjmm.v6i2.19369 Bangladesh J Med Microbiol 2012; 06(02): 7-10